The role of structural empowerment in job distress - hamed heydari; mohammad yazdani ziarat (پژوهش‌های روانشناختی در مدیریت)
Today, successful organizations need employees who have high psychological health. Clearly, structural empowerment are one of the factors that plays an important role in this process. In this study, we have tried to examine impact of structural empowerment on job distress as a measure of employee's psychological health. This study is an applied research, and according to objectives, it ewmployes a descriptive/ Correlative approach. Statistical population of this study included all personnel of the Labor and Social affairs of Qom, and because of the limitation of the population all of them were selected as sample. The research data collection tools were two questionnaires: Kanter's (1977) structural empowerment Questionnaire, and Randolph and Blackburn's (1990) job distress Questionnaire. This questionnaires were used after determining reliability through Cronbach's alpha and Confirm the validity by several experts of in these fields of study. In this study, data obtained from questionnaires have been analyzed by Pearson correlation, liner regression, one sample t tests and Friedman. Findings indicated that all dimensions of structural empowerment include opportunity to learning, having support, access to resources and information, informal and formal power are effective on reducing job distress; and the personnel's structural empowerment and job distress status are at a moderate level.